Partnership Consultation: An Alternative Solution to the Nonexistent Collective Bargaining Right in the Indonesian Ride Hailing Gig Economy Sector - Auditya Firza Saputra (Universitas Airlangga, 2022)
The absence of gig workers’ right to collective bargaining affects the human rights condition of the app drivers. Previous studies roughly fall into two categories: either employing the drivers as a solution or opting for law-making intervention. This paper fills the gap using a new concept based on the United Nations Guiding Principle of Business and Human Rights by exploring the businesses’ social responsibility realm. This qualitative socio-legal research finds that: (1) the clauses of the standardized partnership agreements contain unequal risks allocations, putting the independent contractors in a lose-lose situation; (2) the inability to determine the substantial domain of the contract marginalizes the partners from exercising the related social and economic rights; and (3) the pre-existed structural problems take part as a coercive forces to the partners’ free will to consent, resulting in a doubtful partnership contract validity. As a solution, the insertion of meaningful partnership consultation, a concept adopted from collective bargaining concept in labor relations, enables better mutual consent arrangement and serves as a preemptive remedy to the human rights impact.